Manipulation of the gut microbiota using resistant starch is associated with protection against colitis-associated colorectal cancer in rats - Hu, Y.; Le Leu, R.; Christophersen, Claus; Somashekar, R.; Conlon, M.; Meng, X.; Winter, J.; Woodman, R.; McKinnon, R.; Young, G. (Oxford University Press, 2015)
© The Author 2016. Published by Oxford University Press. All rights reserved. This study evaluated whether dietary resistant starch (RS) and green tea extract (GTE), which have anti-inflammatory and anticancer properties, protect against colitis-associated colorectal cancer (CAC) using a rat model, also investigated potential mechanisms of action of these agents including their effects on the gut microbiota. Rats were fed a control diet or diets containing 10% RS, 0.5% GTE or a combination of the two (RS + GTE). CAC was initiated with 2 weekly azoxymethane (AOM) injections (10 mg/kg) followed by 2% dextran sodium sulphate in drinking water for 7 days after 2 weeks on diets. Rats were killed 20 weeks after the first AOM. Colon tissues and tumours were examined for histopathology by H&E, gene/protein expression by PCR and immunohistochemistry and digesta for analyses of fermentation products and microbiota populations. RS and RS + GTE (but not GTE) diets significantly (P < 0.05) decreased tumour multiplicity and adenocarcinoma formation, relative to the control diet. Effects of RS + GTE were not different from RS alone. RS diet caused significant shifts in microbial composition/diversity, with increases in Parabacteroides, Barnesiella, Ruminococcus, Marvinbryantia and Bifidobacterium as primary contributors to the shift. RS-containing diets increased short chain fatty acids (SCFA) and expression of the SCFA receptor GPR43 mRNA, and reduced inflammation (COX-2, NF-kB, TNF-a and IL-1ß mRNA) and cell proliferation P < 0.05. GTE had no effect. This is the first study that demonstrates chemopreventive effects of RS (but not GTE) in a rodent CAC model, suggesting RS might have benefit to patients with ulcerative colitis who are at an increased risk of developing CRC.